Anthropogenic Activities and Water Quality: A Case of River Satluj, Pakistan: Water Quality of River Satluj (Biological Sciences - PJSIR, 2023)
Pakistan has large freshwater reservoirs and Satluj river is one of them. Length of river Satluj in Pakistan comprises 329 miles. Through the Indus Water Treaty between Pakistan and India, three rivers management has been assigned to India, Satluj is one of them.Pakistan with the help of World Bank, has made water reservoirs and link canals to use the river bed of Satluj. The main objective of study was to find out Water Quality Parameters during the present study seasonally. Overall seven factors were selected for the current study; which were temperature, pH, dissolved oxygen, total dissolved solids, total alkalinity and total hardness. All the water quality parameters under investigation revealed their presence in permissible limits as prescribed by National and International quality guidelines (except dissolved oxygen) and fit for aquatic fauna. Dissolved oxygen remained 4 ppm in summer) and (4.5 ppm in winter) at SZ-1. It might be due the less water discharge and the presence of municipal and industrial wastes at Sulemanki Barrage (study zone-1) of the study area. Moreover, the river water of Satluj investigated throughout the research period indicated that water contamination was due to the various anthropogenic activities.